Recursos genéticos de espécies frutíferas nativas da Amazônia Brasileira - Clement, Charles Roland; Müller, Carlos Hans; Chávez Flores, Wanders Benjamin (Acta Amazonica, 1982)
This article presents the history of the institutional organizations responsable for the study of fruit genetic resources indigenous to the Amazon. The past and present priority lists of CPATU/EMBRAPA, FCAP, INPA/ CNPq, UEPAE/EMBRAPA, CNPMF/EMBRAPA, CEPLAC, CNPSD/EMBRAPA and EPACE are presented, together with the species lists of the germplasm collections and germplasm banks maintained by each institution, as well as discussion of each institution's immediate intentions for the expansion of these studies. Most of the species that appear in the priority list as indigenous to Amazonia are then considered with more detail, as well as several others with eventual economic potential. The uses of these fruits are mentioned and references are made in relation to the threat of genetic erosion faced by each species. The importance of Palmae germplasm is emphasized. General considerations are made about the status of efforts for collecting and conservation of these valuable genetic resources With special reference to the work of CENARGEN/EMBRAPA, about general and specific threats of genetic erosion in the region and some suggestions are made on the strategy for saving these genetic resources.", 'en